2010
DOI: 10.1124/dmd.110.034249
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Carboxylesterase 1 and 2 in the Hydrolysis of Mycophenolate Mofetil

Abstract: ABSTRACT:Mycophenolate mofetil (MMF) is the ester prodrug of the immunosuppressant agent mycophenolic acid (MPA) and is rapidly activated by esterases after oral administration. However, the role of isoenzymes in MMF hydrolysis remains unclear. Although human plasma, erythrocytes, and whole blood contain MMF hydrolytic activities, the mean half-lives of MMF in vitro were 15.1, 1.58, and 3.20 h, respectively. Thus, blood esterases seemed to contribute little to the rapid MMF disappearance in vivo. In vitro anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 25 publications
(21 reference statements)
2
39
0
Order By: Relevance
“…Because these agents are activated by CES1, a possible mechanism for this lack of effect could be the simultaneous administration of immunosuppressive drugs that inhibit CES1. A previous study demonstrated that the immunosuppressive agent, mycophenolate mofetil, was a substrate for CES1 (Fujiyama et al, 2010). Other immunosuppressive agents have not been tested for their activity as esterase inhibitors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because these agents are activated by CES1, a possible mechanism for this lack of effect could be the simultaneous administration of immunosuppressive drugs that inhibit CES1. A previous study demonstrated that the immunosuppressive agent, mycophenolate mofetil, was a substrate for CES1 (Fujiyama et al, 2010). Other immunosuppressive agents have not been tested for their activity as esterase inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme is involved in the metabolism of several therapeutic agents, drugs of abuse, and endogenous compounds. CES1 activates several ester-containing prodrugs, including oseltamivir, dabigatran etexilate, mycophenolate mofetil, and a number of angiotensin-converting enzyme (ACE) inhibitors, including trandolapril, imidapril, benazepril, and quinapril (Takai et al, 1997;Shi et al, 2006;Zhu et al, 2009;Fujiyama et al, 2010;Hu et al, 2013). The enzyme also inactivates a multitude of drugs, including methylphenidate, pethidine, clopidogrel, rufinamide, and oxybutynin (Zhang et al, 1999;Sun et al, 2004;Tang et al, 2006;Williams et al, 2011;Sato et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…CMBL is a relatively novel hydrolysis enzyme, and any potential overlap in its substrates with CES is not well characterized. Cellular localization of these enzymes differs, as CES are present both in the membrane and cytosol (Satoh and Hosokawa, 1998;Fujiyama et al, 2010) whereas CMBL is a predominantly cytosolic enzyme (Ishizuka et al, 2013), emphasizing the need for a careful choice of in vitro system for adequate characterization of hydrolysis. In addition, paraoxonase 1 (PON1), predominantly located in plasma (Bahar et al, 2012), hydrolyzes lactones and aromatic carboxylic acid esters (Fukami and Yokoi, 2012;Ishizuka et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…MMF metabolizes into MPA in the liver, and it is non-competitive and a reversible inhibitor of IMP dehydrogenase enzyme, resulting in the inhibition of the de novo pathway of guanine nucleotide synthesis. This directly diminishes the proliferation of T and B lymphocytes and also suppresses antibody formation [4,5]. Prednisolone, chemically known as (8S,9S,10R,11S,13S,14S,17R)-11,17-dihydroxy-17-(2-hydroxyacetyl)-10,13-dimethyl-7, 8,9,11,12,14,15,16-octahydro-6H-cyclopenta[a]phenanthren-3-one is a glucocorticoid that has anti-infl ammatory action [6,7].…”
Section: Introductionmentioning
confidence: 98%